Solar sail trajectory optimization for interplanetary missions: part I—dynamics and optimal control - Chak, Yew Chung; Varatharajoo, Renuganth; Razoumny, Yury (Springer Science and Business Media Deutschland Gmbh, 2025)
Solar sailing enables low-cost, continuous-acceleration interplanetary missions without fuel consumption. This paper presents the modeling and trajectory optimization of solar sail spacecraft for minimum-time interplanetary transfers. The solar radiation pressure model is formulated, and the spacecraft equations of motion under continuous low-thrust conditions are derived. The sequential quadratic programming (SQP) optimization method is used to solve the minimum-time trajectory problem, providing optimal steering profiles for two-dimensional circle-to-circle Earth–Mars and Earth–Venus transfers. The results form the foundation for developing intelligent controllers capable of replicating optimal trajectories without a real-time optimization.